2019
DOI: 10.1186/s12875-019-1013-9
|View full text |Cite
|
Sign up to set email alerts
|

Health TAPESTRY: co-designing interprofessional primary care programs for older adults using the persona-scenario method

Abstract: Background Working with patients and health care providers to co-design health interventions is gaining global prominence. While co-design of interventions is important for all patients, it is particularly important for older adults who often experience multiple and complex chronic conditions. Persona-scenarios have been used by designers of technology applications. The purpose of this paper is to explore how a modified approach to the persona-scenario method was used to co-design a complex primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 24 publications
1
46
1
Order By: Relevance
“…The co-created persona scenarios provided a narrative and insight into the lived experience of people with particular disabilities and health conditions, in a context and over time. This is in line with [14] who conducted similar types of persona-scenario workshops with patients and clinicians for a primary care intervention. They also found that this method provided rich descriptions and argue that the quality and quantity of ideas that were identified were significant and illustrate the added value and strength of this method.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The co-created persona scenarios provided a narrative and insight into the lived experience of people with particular disabilities and health conditions, in a context and over time. This is in line with [14] who conducted similar types of persona-scenario workshops with patients and clinicians for a primary care intervention. They also found that this method provided rich descriptions and argue that the quality and quantity of ideas that were identified were significant and illustrate the added value and strength of this method.…”
Section: Discussionsupporting
confidence: 83%
“…Donald et al [13] had positive experiences of using personas in a consensus workshop with patients, and suggests using personas in patient-oriented research to explore their needs and preferences. Valaitis et al [14] have involved patients and clinicians in persona-scenario workshops for a primary care intervention.…”
Section: Persona Use In Research and The Industrymentioning
confidence: 99%
“…Where reported, public participant numbers ranged from 4 [ 83 ], to an estimated 1200 [ 84 ], though no numbers were given in 13 articles (14.0%) [ 45 , 47 , 49 , 58 , 69 , 72 74 , 77 , 85 88 ], and incomplete or estimated numbers were provided in a further 25 (26.9%) [ 40 , 43 , 44 , 50 , 51 , 56 , 57 , 61 – 63 , 66 , 76 , 82 , 84 , 89 99 ]. Some authors provided demographic data of public participants, such as age, gender, medical condition and/or race, however, there was no detail provided in more than half of articles ( n = 52, 55.9%) [ 37 , 38 , 40 , 41 , 43 – 51 , 55 , 58 , 59 , 61 , 63 , 66 , 68 , 69 , 71 74 , 77 , 79 , 81 – 88 , 93 , 95 110 ]. There were no studies where IAP2 public involvement level was rated as ‘Inform’, or ‘Empower’.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the reported outcome was outlined in less than half of studies ( n = 39, 43.3%) [ 38 , 41 45 , 47 50 , 53 , 54 , 56 59 , 61 , 65 , 66 , 68 71 , 80 , 81 , 83 85 , 87 , 92 , 93 , 99 , 102 , 105 , 107 , 109 , 110 , 123 , 131 ] (Additional file 2 ). Some evaluations were reported additionally [ 59 , 70 , 107 ] or exclusively [ 50 , 53 , 61 , 66 , 71 , 76 , 81 , 83 , 85 , 102 , 123 , 131 ] in separate publications.…”
Section: Resultsmentioning
confidence: 99%
“…In the rst phase, we conducted a qualitative study employing the persona-scenario method to co-design a set of generic design speci cations that could be applied to any ICT [21]. This innovative design approach engages users to inform program or resource development in a way that centralizes their perspectives when determining user requirements [22,23,24].…”
Section: Introductionmentioning
confidence: 99%